REGIONAL INTEGRATION AND INTRA OIC TRADE: LESSONS FROM INDONESIA AND MALAYSIA - Wardani, Dyah Titis Kusuma (Jurnal Ekonomi & Studi Pembangunan, 2016)
In addition to their membership in the Organization of Islamic Cooperation (OIC), Indonesia and Malaysia are also involved as active members in the evolving Association of South-East Asian Nation (ASEAN). This raises a question over whether involvement in the ASEAN, especially how ASEAN Free Trade Area (AFTA) brings about a negative or positive impact on Indonesia’s and Malaysia’s trade performance with fellow OIC member countries. The current paper attempts to examine empirically the likelihood of such relationship and explore whether there presents a systematic difference between the case of Indonesia and Malaysia. Based on the results, some implications will be highlighted and policy recommendations will be offered.